Aliança com a morte: uma reflexão sobre Isaías 28-32 - Santos, Virginia Inacio dos (2009)
The book of Isaiah has been the subject of many studies among researchers and critics, both in terms of its authorship and aspects of its language, content and form. We believe that all these aspects and approach have not exhausted the issues that could be analyzed, and many questions are still open. Reflecting on chapters 28-32 of Isaiah, which deal with the issue of the covenant with death and the pride of the drunkards of Ephraim, will allow us to analyze whether Isaiah was the author of a new theological concept of alliance. Hypothetically, we believe that Isaiah formed or created the concept of "covenant with death". Our work will bring a critical analysis of this hypothesis in an attempt to provide convincing results that aim to legitimize and confirm our suspicion. Yahweh's covenant with his people, such a common theme in Old Testament prophecy, is present in these chapters of Isaiah which speak of his reversal and the attempt to restore them. In Isaiah, in the block under study, the alliance is no longer with Yahweh and becomes with death tw<m'-ta, tyrIb> "covenant with death" The impression given to the reader is that Isaiah contests the new way of life of the Jews and not having much success in the reception of their prophetic sayings, sees the increase of the crisis and loss of identity of Jerusalem and Judah. Our research will seek to understand this new concept of alliance in the block under study. It will seek to understand if the prophet when speaking of the "covenant with death" elaborates a new concept of alliance or just questions the inversion of the values ​​of the old alliance between the Israelite people and Yahweh. By deepening the block, the research will enable a critical analysis of some problems raised by the prophet himself, such as the issues related to calm and peaceful women who will lament in their breasts. Another subject that we intend to approach with attention is the question of the crown of arrogance of those taken by wine, priests and prophets included in this group. Therefore, how to understand the elaboration of a new theology of the alliance, that is, "alliance with death", within the presuppositions of noble women and the drunkenness of the political and religious nobility? Is the prophet in this attitude criticizing the Old Testament concepts of the covenant, or just noting its breach and alerting to the fact that it must be restored at all costs? (AU) The thesis is structured in several chapters: "Chapter 1. Speaking and knowing a little more about Isaiah 28-32"; "Chapter 2. Theological Emphases Supporting the Block - Isa 28-32"; "Chapter 3. The Covenant with Death: Women, Prophets, and Priests"; It also has two appendices: "Appendix 1- Interlinear translation" and "Appendix 2 - The text in pericopes" breaches of alliance - Israelite religion - denunciation - international alliances - women - drunkenness of the priests and prophets - family - prophetic mission - destruction of Ephraim - Ariel - announcement of the destruction of Assyria - oracles - announcement of the righteous king - Yahweh of hosts - saint of Israel - Door Concept - Judging - Justice - Judgment - The Rest - Your People - My People - Zion Tradition - Covenant Tradition - Evil Spirit - Spirit - Prophetesses - Mothers - Poor and Widows - Autonomous - Political and Politicized - Peaceful Women - confident daughters - wine Isaiah 31,1-9 - Isaiah 32,1-20 - Isaiah 29,21 - Isaiah 28,7-13 - Isaiah 28,14-22 - Isaiah 28,1-6 - Isaiah 29,9-16 - Isaiah 30, 1-17 - Isaiah 31,1-3 - Isaiah 32,9-14 - Isaiah 33,7-16 - Isaiah 28,1-29 - Isaiah 29,1-24 - Isaiah 30,1-33 (AU)